IMPLEMENTASI PENDEKATAN EKSPOSITORI DALAM MENINGKATKAN HASIL BELAJAR PKn - salfitri . (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This research was carried out aimed at improving student learning outcomes in Civics in the Central Government living system through the use of an Expository Approach in class IV-A of SD Negeri 1 Peureulaksemen II in the 2017-2018 Academic Year. The benefits of this research are to add new references and theories in the field of education, especially in the implementation of Classroom Action Research by applying various models or learning methods so as to improve student learning outcomes. To achieve this, the step that needs to be implemented is to use the Expository Approach. Data analysis method used in this study uses descriptive analysis whose data is sourced from formative tests and classroom observations. Sampling amounted to 30 people in class IV-A. Retrieval of learning outcomes data using learning outcomes test instruments and observation sheets. From the results of the first cycle test, showed that students who scored 80 were 2 students (6.66%), while those who scored 75 were 11 students or (36.67%), who scored 70 as many as 6 students or (20% ), those who get 65 are 8 students or (26.67%), those who get 60 are 2 students or (6.67%) while the lowest score of 50 is 1 student (3.33%). Based on the completeness of student learning from a total of 30 students there are 19 students or (63.33%). Whereas in Silkus II who got a very good score that is 90 as many as 3 students or (10%), who got a score of 85 as many as 6 students or (20%) who scored 80 as many as 7 students or (23.33%) who scored 75 as many as 5 students or (16.66%) who scored 70 as many as 6 students or (20%) while those who scored 65 were 2 students or (6.66%) and those who got the lowest scores were 60 students or 1 , 33%). The average value of the class is 77.50 with 90% completeness. Based on this research it can be concluded that the application of the Expository Approach can improve the learning outcomes of Civics subjects, especially the material